Optimasi Penugasan Pekerja Menggunakan Metode Hungarian Modifikasi pada Proyek Pembangunan Jembatan X di Kabupaten Timor Tengah Utara - Prima Mersi Angela Klaran; Yoseph P. K. Kelen; Fried Markus Allung Blegur; Faustianus Luan (Journal of Mathematics Theory and Applications, 2022)
Assignment problems that are often encountered in local life are problems related to the optimal allocation of various productive resources or personnel that have different levels of efficiency for different jobs. The Hungarian method can be used to solve balanced assignment problems, namely the number of workers is equal to the number of jobs and unbalanced assignments, and namely the number of workers is not the same as the number of jobs. The assignment problem in this study is an unbalanced assignment problem where the number of workers is 90 (ninety) people divided into 4 (four) work teams while the number of work items is as much as 7 (seven) work items. This assignment can be completed by applying a modified Hungarian method with the aim of minimizing work completion time, worker wages and minimizing completion time and worker wages together. From the research results, after using the modified Hungarian method, the optimal total time is 25 days with the optimal total cost of IDR 57,080,000 and the combined completion time and total wages calculated jointly is 87.3.